Role of bicarbonate as a pH buffer and electron sink in microbial dechlorination of chloroethenes - Delgado, Anca G (BioMed Central, 2012)
BACKGROUND: Buffering to achieve pH control is crucial for successful trichloroethene (TCE) anaerobic bioremediation. Bicarbonate (HCO(3)(−)) is the natural buffer in groundwater and the buffer of choice in the laboratory and at contaminated sites undergoing biological treatment with organohalide respiring microorganisms. However, HCO(3)(−) also serves as the electron acceptor for hydrogenotrophic methanogens and hydrogenotrophic homoacetogens, two microbial groups competing with organohalide respirers for hydrogen (H(2)). We studied the effect of HCO(3)(−) as a buffering agent and the effect of HCO(3)(−)-consuming reactions in a range of concentrations (2.5-30 mM) with an initial pH of 7.5 in H(2)-fed TCE reductively dechlorinating communities containing Dehalococcoides, hydrogenotrophic methanogens, and hydrogenotrophic homoacetogens. RESULTS: Rate differences in TCE dechlorination were observed as a result of added varying HCO(3)(−) concentrations due to H(2)-fed electrons channeled towards methanogenesis and homoacetogenesis and pH increases (up to 8.7) from biological HCO(3)(−) consumption. Significantly faster dechlorination rates were noted at all HCO(3)(−) concentrations tested when the pH buffering was improved by providing 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) as an additional buffer. Electron balances and quantitative PCR revealed that methanogenesis was the main electron sink when the initial HCO(3)(−) concentrations were 2.5 and 5 mM, while homoacetogenesis was the dominant process and sink when 10 and 30 mM HCO(3)(−) were provided initially. CONCLUSIONS: Our study reveals that HCO(3)(−) is an important variable for bioremediation of chloroethenes as it has a prominent role as an electron acceptor for methanogenesis and homoacetogenesis. It also illustrates the changes in rates and extent of reductive dechlorination resulting from the combined effect of electron donor competition stimulated by HCO(3)(−) and the changes in pH exerted by methanogens and homoacetogens.